A Note on the Land Acquisition Act of Singapore and Social Re-Engineering - Ameen Talib (International Journal Labs, 2023)
Land Acquisition Act (LAA) of Singapore regulates the compulsory acquisition of land in Singapore. This paper looks at LAA and its’ role in shifting the land ownership structure in Singapore and the resultant social re-engineering. The LAA had four prominent features which were, (1) power to obtain private land by the state, (2) inability of affected landowners to object the compulsory acquisition, (3) landowners being compensated much less than market value (prior to 2007), and (4) the formation of an Appeals Board to formally judge on compensations. The research would like to reveal LAA and its role in changing the land ownership structure in Singapore and the resultant social re-engineering. The method of writing this article uses literature reviews from journals and references related to Land Acquisition Act. Search for literature on performance using Google Scholar and other relevant platforms. The researcher also used other relevant documents, including physical documents, to gain more knowledge on the topic discussed. The LAA indeed resulted in the lives of many to be better-off but it was at the expense of a few wealthy families in Singapore.